Performance Testing of Twisted Pair Cables. (12th March 2008) - Mahmoud, Ahmed F.; Abdallah, Mahmoud I.
Abstract : This work introduces characteristics of twisted pair cables which play an important role in transferring data. In this paper, category 5 enhanced as a type of unshielded twisted pair cables was selected to verify all tests on it according to ISO/IEC 11801 as one of international standard specifications. Random samples were selected from cables market. All tests were done on these samples to make sure of using validity and complying with the international standard. After testing the selected samples, it is found that4 % are not satisfying the international standard specification while as96 % are satisfying the international standard specification.